Four new species of Callibaetis Eaton (Ephemeroptera: Baetidae), nymphal description of Callibaetis (Abaetetuba) fasciatus (Pictet) and keys for South American species of Callibaetis - Cruz, Paulo Vilela; Salles, Frederico Falcão; Hamada, Neusa (Zootaxa, 2017)
The first phylogenetic study of Callibaetis Eaton indicated an unrevealed diversity in this genus, including four new species named as Callibaetis sp. A, B, C and D, and the undescribed nymph of Callibaetis (Abaetetuba) fasciatus (Pictet). Given that neither the nymph of C. (Ab.) fasciatus nor the four new species received a proper description, the objective of this study is to describe them. The nymph of C. (Ab.) fasciatus differs from the others species in the subgenus by the presence of one row of setae on basal part of inner-dorsal row of maxilla and metanotum without spines; Callibaetis sp. A is described as Callibaetis (Abaetetuba) cochlea sp. nov. and differs from the others species in the subgenus by having trapezoid segment III of labial palp in nymphs; Callibaetis sp. B is described as Callibaetis (Aiso) calophenigyn sp. nov. and differs from the others species in the subgenus by the absence of stout setae on dorsal surface of glossa in nymphs, and from the others species in the genus by the forewing with red C and Sc areas in female imago; Callibaetis sp. D is described as Callibaetis (Callibaetis) molinerii sp. nov. and differs from the others species in the subgenus, from South America, by the maxilla with tuft of stout setae on outer margin proximad of palp insertion and paraglossa without row of stout setae on ventral surface; Callibaetis sp. C is described as Callibaetis (Cunhaporanga) imperator sp. nov. and differs from the others species in the subgenus by the presence of a complete row of setae on outer margin of maxilla. Additionally, new keys for species of Callibaetis from South America are proposed.